Factors Affecting Management Performance: Survey on Community Empowerment Managers in Bekasi Regency - Rudy Rosdiana (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2021)
Community empowerment is one of the government's programs in alleviating poverty in Indonesia. The success of implementing community empowerment cannot be separated from the program's role. This study aims to determine what factors affect the performance of the empowerment program implementers. The research method uses a descriptive approach to obtain an overview of the facts in the field and path analysis to determine the effect of research variables. The research respondents were the implementers of the community empowerment program in Bekasi Regency as many as 48 people. The results showed that there was a significant effect of Work Attitude (X1), Work Climate (X2), and Work Motivation (X3) on Performance (Y) of 0.815, and the remaining 0.185 or 18.5% influence by other variables not included in this study. The study results recommend improving performance through training and coaching on an ongoing basis to improve implementing empowerment programs.